Śiva or Brahma? The “Masque Court” at the Bibliothèque Nationale, Paris - Falk, Harry (Indo-Iranian journal, 2013)
A number of “masks” cast in metal are known from the North-West, particularly Kashmir and Himachal Pradesh. They are not used as theatre masks, they lack openings for view or speech, and are found in temples fixed to a wall. One, found near Peshawar in Gandhara is conspicuous by its artistic beauty. It is inscribed on its lower rim; both script and style allow to date it in the middle or late Gupta period. The inscription has been read and interpreted by G. Fussman, who assumed that some of his readings would need revision. A new reading is proposed and discussed here, as it admits of two rather divergent interpretations.